Apicultural activity as a supervised agricultural activity - Różański, Krzysztof (Przegląd Prawa Rolnego, 2025)
This article aims to answer the question of whether apicultural activity, no matter if done as a hobby or professionally, fits into the category of supervised agricultural activity. It also explains the consequences of such categorisation, and highlights discrepancies arising from the provisions of EU Regulation No. 2016/429 on transmissible animal diseases and the Polish Act on Animal Health Protection and Control of Infectious Animal Diseases. It is proposed that the provisions on supervised activities could apply to both amateur and professional apicultural activity and there is a potential opportunity for harmonising EU and the national law in this area through the adoption of a new Animal Health Protection Act currently being drafted by the Ministry of Agriculture and Rural Development.